Whose Grave's This, Sir?: An Ethico-Political Critique of Organized Resting Places - Pianezzi, Daniela (Business ethics quarterly, 2025)
What can we learn about organizational ethics from studying cemeteries as organizational/organized manifestations of our mutual, embodied vulnerability? How does, and how should, the ethico-political imperative of death and the deceased materialize in the cemeterial space? With reference to a comparative analysis of two island cemeteries, Venice's San Michele and New York's Hart Island, this paper makes three contributions to the emerging literature on organizational ethics of life and death. First, it makes an empirical contribution based on an organizational study of two "resting places" that highlights the importance of understanding organizational life and death with reference to ethics. Second, it makes a theoretical contribution to scholarship on the organization of death and on grieving as embedded in a politics and ethics of recognition. Third, the paper shows how our desire to be recognized as valid, viable subjects comes to be organized, and situated, in ways that perpetuate precarity and vulnerability, a point that is illustrated with reference to cemeteries as ethically significant organizational settings.